Examining modification of the associations between air pollution and birth outcomes by neighborhood deprivation in a North Carolina birth cohort, 2011–2015 - Cowan, Kristen N.; Krajewski, Alison K.; Jimenez, Monica P.; Luben, Thomas J.; Messer, Lynne C.; Rappazzo, Kristen M. (Frontiers in Reproductive Health, 2024)
Background Evidence from studies of air pollutants and birth outcomes suggests an association, but uncertainties around geographical variability and modifying factors still remain. As neighborhood-level social characteristics are associated with birth outcomes, we assess whether neighborhood deprivation level is an effect measure modifier on the association between air pollution and birth outcomes in a North Carolina birth cohort. Methods Using birth certificate data, all North Carolina residential singleton live births from 1 January 2011 to 31 December 2015 with gestational ages of 20–44 weeks (n = 566,799) were examined for birth defect diagnoses and preterm birth. Exposures were daily average fine particulate matter (PM2.5), daily 8-h maximum nitrogen dioxide (NO2), and daily 8-h maximum ozone (O3) modeled concentrations, and the modifier of interest was the neighborhood deprivation index (NDI). Linear binomial models were used to estimate the prevalence differences and 95% confidence intervals (CI) for the association between ambient air pollution and birth defect diagnoses. Modified Poisson regression models were used to estimate risk differences (RDs) and 95% CIs for air pollution and preterm birth. Models were stratified by the neighborhood deprivation index group (low, medium, or high) to assess potential modification by NDI. Results Approximately 3.1% of the study population had at least one birth defect and 8.18% were born preterm. For preterm birth, associations with PM2.5 and O3 did not follow a conclusive pattern and there was no evidence of modification by NDI. The associations between NO2 and preterm birth were generally negative across exposure windows except for a positive association with NO2 and preterm birth for high NDI [RD: 34.70 (95% CI 4.84–64.56)] for entire pregnancy exposure. There was no evidence of associations between pollutants examined and birth defects. Conclusions There may be differences in the association between NO2 exposure and preterm birth by NDI but we did not observe any evidence of associations for birth defects. Our results support the public health protection afforded by reductions in air pollution, even in areas of neighborhood deprivation, but future research conducted in areas with higher levels of air pollution and evaluating the potential for modification by neighborhood deprivation level would be informative.